2019
DOI: 10.1021/acs.biochem.9b00111
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Stability Adaptation of a Double-Stranded RNA-Binding Domain to Transfer RNA Ligand

Abstract: The double-stranded RNA-binding domain (dsRBD) is a broadly distributed domain among RNA-maturing enzymes. Although this domain recognizes dsRNA's structures via a conserved canonical structure adopting an α 1 −β 1 β 2 β 3 −α 2 topology, several dsRBDs can accommodate discrete structural extensions expanding further their functional repertoire. How these structural elements engage cooperative communications with the canonical structure and how they contribute to the dsRBD's overall folding are poorly understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…These structures have confirmed the common domain architecture of Dus enzymes consisting of an N-terminal domain adopting a TIM-BARREL fold wherein the binding site of the FMN redox coenzyme lies in its centre, and a C-terminal helical domain formed by 4-helix bundle, which is dedicated to tRNA recognition [16,18]. Apart from these two strictly conserved protein domains, there are additional domains that are exclusively observed among certain members of eukaryotic Dus [15,22,23].…”
Section: Introductionsupporting
confidence: 60%
“…These structures have confirmed the common domain architecture of Dus enzymes consisting of an N-terminal domain adopting a TIM-BARREL fold wherein the binding site of the FMN redox coenzyme lies in its centre, and a C-terminal helical domain formed by 4-helix bundle, which is dedicated to tRNA recognition [16,18]. Apart from these two strictly conserved protein domains, there are additional domains that are exclusively observed among certain members of eukaryotic Dus [15,22,23].…”
Section: Introductionsupporting
confidence: 60%
“…We have recently shown that the recognition mechanism of the tRNA substrate by Homo sapiens Dus2 (hDus2 or Dus2L) is much more complex than that observed in bacterial enzymes (Figure ). Indeed, hDus2 has a structural insertion within the TIM-barrel and an additional double-stranded RNA binding domain (dsRBD) that is appended to the polypeptide just after the HD, both playing a role in tRNA recognition (Figures and ). ,, The dsRBD is a double-stranded RNA (dsRNA) recognition module and is mainly found in proteins involved in mRNA transport, processing or editing. Our structures of the hDus2 dsRBD in complex with a dsRNA (Figure C), as well as in-depth investigations by site-directed mutagenesis, nuclear magnetic resonance (NMR), and small-angle X-ray scattering (SAXS) of the interaction of the dsRBD with human tRNA Lys 3 revealed how this domain binds to tRNA. Indeed, this domain has a particular mode of tRNA recognition involving, in addition to the well-known canonical interactions between dsRBDs and dsRNAs (ribose and phosphate recognition), specific interactions with RNA, i.e., hydrogen bonds between some residues of dsRBD and RNA bases.…”
Section: Dihydrouridine Synthase Enzymes: Structure–function Relation...mentioning
confidence: 97%
“…122 Indeed, hDus2 has a structural insertion within the TIM-barrel and an additional double-stranded RNA binding domain (dsRBD) that is appended to the polypeptide just after the HD, both playing a role in tRNA recognition (Figures 5 and 6). 103,122,123 The dsRBD is a double-stranded RNA (dsRNA) recognition module and is mainly found in proteins involved in mRNA transport, processing or editing. 124−127 Our structures of the hDus2 dsRBD in complex with a dsRNA (Figure 6C), as well as in-depth investigations by site-directed mutagenesis, nuclear magnetic resonance (NMR), and small-angle X-ray scattering (SAXS) of the interaction of the dsRBD with human tRNA Lys 3 revealed how this domain binds to tRNA.…”
Section: ■ Dihydrouridine Synthase Enzymes: Structure−function Relati...mentioning
confidence: 99%
“…Bou-Nader et al [ 130 ], Guimaraes and Golinelli-Pimpaneau [ 131 ], Molinaro et al [ 132 ], Whelan et al [ 133 ].…”
Section: Additional References From Figuresmentioning
confidence: 99%